1983
DOI: 10.1021/ic00149a004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of the copper(III)-tripeptide complex of tri-.alpha.-aminoisobutyric acid

Abstract: On the other hand, the cleavage, nitrogen inversion, and recombination of each of the copper-nitrogen bonds in [Cu(tet b) (blue)]1 2 3"1" lead to the formation of extremely unstable isomers as shown in Figure 7. The existence of each of these extremely unstable species is highly unlikely. Presumably this is the reason that there is no blue-to-red interconversion occurring concurrently with its dissociation in strongly acidic media. In addition to [Cu(tet b) (blue)]2"1", tet b forms two relatively stable red co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 2 publications
4
56
0
Order By: Relevance
“…The shortest coordination distance is always the organometallic Cu1ÀC1 bond, which ranges from 1.848 for 1 to 1.926 for 6. This is in agreement with the fact that the macrocyclic ligand, L 1 , of complex 1 has the smallest cavity of this series and also with the fact that the longest Cu1ÀC1 distance is that of complex 6, which contains a ligand, L 6 , with a tertiary amine. The trans effect produced by the Cu1 À C1 bond generates the longest Cu À N distances (Cu1ÀN2 bond lengths range from 1.995 for 3 to 2.048 for 6) and are 0.033-0.095 longer than the mean distances of the other two CuÀN bonds (Cu1ÀN1 and Cu1À N3).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The shortest coordination distance is always the organometallic Cu1ÀC1 bond, which ranges from 1.848 for 1 to 1.926 for 6. This is in agreement with the fact that the macrocyclic ligand, L 1 , of complex 1 has the smallest cavity of this series and also with the fact that the longest Cu1ÀC1 distance is that of complex 6, which contains a ligand, L 6 , with a tertiary amine. The trans effect produced by the Cu1 À C1 bond generates the longest Cu À N distances (Cu1ÀN2 bond lengths range from 1.995 for 3 to 2.048 for 6) and are 0.033-0.095 longer than the mean distances of the other two CuÀN bonds (Cu1ÀN1 and Cu1À N3).…”
Section: Resultssupporting
confidence: 87%
“…The non-anionic nature of the nitrogen-coordinating atoms is in line with the longest Cu III ÀN bonds found in this family of complexes relative to the bond lengths found in other Cu III complexes that contain deprotonated amides as ligands. [6,19] In complexes 1-3, 5, and 6 the ClO 4 À or CF 3 SO 3 À counteranions or a water molecule (in the case of complex 6) are weakly associated with the metal center, generating a decompressed tetragonally distorted octahedral environment in which one of the CuÀO distances is substantially longer than the other (see Table 2). In all cases, the longer CuÀO distance is located on the same side of the macrocycle as the NÀH or NÀMe bonds, whereas the shorter CuÀO distance is located on the other side which has a much lower steric encumbrance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cu III state is stabilized by strong coordinating ligands, and its complexes have been isolated as carboxylates, [4] thiolates, [5] deprotonated amides, [6] carbamates, [7] and N-confused porphyrins. [8] The CuÀC(sp 2 ) bonds in the Nconfused porphyrins are stabilized by the p-delocalization effect in the porphyrin ring aided by protonation-deprotonation of the peripheral nitrogen atoms.…”
mentioning
confidence: 99%
“…[7][8][9][10][11]13 Margerum and co-workers have investigated and characterized several Cu(II) and Cu(III) complexes with some peptides with respect to their reactivity, structure and products. [43][44][45][46][47] These studies showed that Cu(III) complexes with tripeptides or tetrapeptides decompose with rapid oxidative degradation of the peptides. In addition, some of the authors 29 suggested Cu(III) as an intermediate in the oxidative degradation and cleavage of DNA in reactions involving Cu II GGHG/H 2 O 2 /ascorbic acid (GGHG = glycylglycylhistidylglycine).…”
Section: Mechanism Of Copper Peptides Oxidation In the Presence Of S(mentioning
confidence: 99%